Life-threatening arrhythmias with autosomal recessive TECRL variants. Issue 5 (25th December 2020) - Webster, Gregory; Aburawi, Elhadi H; Chaix, Marie A; Chandler, Stephanie; Foo, Roger; Islam, A K M Monwarul; Kammeraad, Janneke A E; Rioux, John D; Al-Gazali, Lihadh; Sayeed, Md Zahidus; Xiao, Tingting; Zhang, Han; et al.
Abstract: Aims : Sudden death and aborted sudden death have been observed in patients with biallelic variants in TECRL . However, phenotypes have only begun to be described and no data are available on medical therapy after long-term follow-up. Methods and results : An international, multi-centre retrospective review was conducted. We report new cases associated with TECRL variants and long-term follow-up from previously published cases. We present 10 cases and 37 asymptomatic heterozygous carriers. Median age at onset of cardiac symptoms was 8 years (range 1–22 years) and cases were followed for an average of 10.3 years (standard deviation 8.3), right censored by death in three cases. All patients on metoprolol, bisoprolol, or atenolol were transitioned to nadolol or propranolol due to failure of therapy. Phenotypes typical of both long QT syndrome and catecholaminergic polymorphic ventricular tachycardia (CPVT) were observed. We also observed divergent phenotypes in some cases despite identical homozygous variants. None of 37 heterozygous family members had a cardiac phenotype. Conclusion : Patients with biallelic pathogenic TECRL variants present with variable cardiac arrhythmia phenotypes, including those typical of long QT syndrome and CPVT. Nadolol and propranolol may be superior beta-blockers in this setting. No cardiac disease or sudden death was present in patients with a heterozygous genotype.